Antibiotic Susceptibility Pattern in Clinical Isolates of Pseudomonas aeruginosa - Wahyunita Do Toka; Rizalinda Sjahril; Firdaus Hamid (Nusantara Medical Science Journal, 2021)
Introduction: Pseudomonas aeruginosa is an opportunistic pathogen and causes of nosocomial infections in hospitals. Due to high antibiotic resistance and the ability to develop new resistance during antibiotic treatment, Pseudomonas aeruginosa infection is difficult to eradicate because the physical treatment becomes difficult and ineffective. This study was conducted to evaluate the antibiotic sensitivity pattern of Pseudomonas aeruginosa strains at two different hospital in Makassar. Methods: This study is a cross-sectional study from March to May 2021. The research samples were taken from the results of culture and antibiotic sensitivity tests conducted at two different hospital, Hasanuddin University Hospital and Dr. Wahidin Sudirohusodo Hospital for the period January 1 to September 30, 2019. A total of 84 samples were cultured and tested for antibiotic sensitivity of Pseudomonas aeruginosa. Results: Antibiotic sensitivity of Pseudomonas aeruginosa was best with aminoglycoside antibiotics, gentamicin (100%) at Hasanuddin University Hospital and amikacin (95.8%) at Dr. Wahidin Sudirohusodo Hospital. At Hasanuddin University Hospital followed by antibiotics amikacin (92.3%) and meropenem (84.6%). At Dr. Wahidin Sudirohusodo Hospital, Pseudomonas aeruginosa also showed good sensitivity to gentamicin (91.5%) and meropenem (77.5%). The sensitivity of Pseudomonas aeruginosa was lowest to piperacillin/tazobactam. Conclusions: This study shows that the level of effectiveness of the antibiotics meropenem, amikacin and gentamicin is high enough and it can be used as a treatment option in Pseudomonas aeruginosa infection. This study can help as a reference to prevent mortality and morbidity associated with Pseudomonas aeruginosa infection.